2011
DOI: 10.1007/s12264-011-1530-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in neurodegeneration: potential benefits of non-steroidal anti-inflammatories

Abstract: Abstract:The cellular messenger nitric oxide (NO) has been linked to neurodegenerative disorders due to the increased expression of the enzymes that catalyze its synthesis in postmortem tissues derived from sufferers of these diseases. Nitrated proteins have also been detected in these samples, revealing that NO is biologically active in regions damaged during neurodegeneration. Modulation of NO levels has been reported not only in the neurons of the central nervous system, but also in the glial cells (microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 131 publications
0
59
0
Order By: Relevance
“…NO is released from activated microglia, and neurons are remarkably sensitive to NO-induced cell death [2]. High levels of NO produced by iNOS from activated microglial cells are associated with the progression of various neurodegenerative diseases [8]. ROS are also strongly associated with microglial neuroinflammatory processes in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…NO is released from activated microglia, and neurons are remarkably sensitive to NO-induced cell death [2]. High levels of NO produced by iNOS from activated microglial cells are associated with the progression of various neurodegenerative diseases [8]. ROS are also strongly associated with microglial neuroinflammatory processes in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that medium from M1 macrophages is toxic to cortical neurons [51][52][53] . NO, glutamine and reactive oxygen species produced by M1 macrophages or microglia are generally accepted to lead to neuronal degeneration in MS [54][55][56] . Sodium channel blockade can rescue axons from NO-mediated degeneration in EAE [57,58] .…”
mentioning
confidence: 99%
“…24) In this context, compounds that can modulate the neuroinflammatory processes may prove useful in the control of neurodegeneration. 2,23) Both 4-methylcoumarin compounds investigated in this study were able to exert anti-inflammatory effects in primary rat microglial cultures, evidenced by inhibition of proinflammatory and neurotoxic mediators NO, PGE 2 , TXB 2 and TNF-α production and also by lowering iNOS and COX-2 protein expression, but without any significant effect on COX-1 and COX-2 enzyme activities in whole blood assay.…”
Section: Discussionmentioning
confidence: 87%
“…3,4,23) Microglia, which are the main cellular components of the brain immune system, play an important role in the process of inflammation in the CNS 3) and their chronic activation may contribute to the development and progression of neurodegenerative diseases. 24) In this context, compounds that can modulate the neuroinflammatory processes may prove useful in the control of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation